PENGGUNAAN STRATEGI PEMBELAJARAN AKTIF EVERYONE IS A TEACHER HERE (ETH) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII - Sri Yunita Ningsih; Gustimalasari Gustimalasari (MES: Journal of Mathematics Education and Science, 2018)
Abstract. This research has been made to know skill of student’s concept by using active learning strategy everyone is teacher here (ETH). Beside that this study aims to measure student’s concept understanding with statistical test between Experimental Class (Active Learning Strategy Everyone Is Teacher Here) and control class (Conventional Learning ). The population was seventh grade of SMPN 3 Lirik consist 94 students in three classes. Sample was took randomly, experiment class ( VII.2 ) and control class ( VII.I ) This research was experiment, the form of this research was Quasi Experimental Design with randomized subject posttest only control group design. based on statistic data processing has been retrieved - t hitung -3,159 smaller than - t table was -2,000 and based on t test has been retrieved -thitung -t table so Ho rejected and Ha received. So that the writer conclude that skill of math student’s concept understanding by using active learning Strategy Everyone Is Teacher Here (ETH) is better than conventional concept understanding.Keywords: Everyone Is A Teacher Here, Concept Understanding